Outcome of abdominal massage before gavage feeding on tolerated feeding for low birth weight infants - Abdelaziz Hendy; Nahed Saied El‐Nagger; Ahmed Abozeid; Fadia Ahmed Reshia; Shahenda A. Salih; Manar Fayez Alruwaili; Ahmed Hendy (Wiley, 2022)
Abstract Aim To assess the effect of abdominal massage pre‐gavage feeding on tolerated feeding for low birth weight (LBW) infants. Methods An experimental research design at a government hospital at Egypt. Purposive sample composed of LBW infants was randomly divided into study and control groups each with 60 LBW infants. Results A total of 55% of the participants in the study group grew sleepy, whereas only 15% of the studied participants in the control group grew sleepy. The abdominal circumference after feeding in the study group was 23.18 ± 2.99 cm, whereas that in the control group was 24.79 ± 2.99 cm. The gastric residual volume in the study group was 0.8 ± 0.10 ml, whereas that in the control group was 3.86 ± 1.03 ml. Conclusion Finally, abdominal massage had a positive impact on the postfeeding state of alertness and feeding tolerance.